Absence of giant blood Marseille‐like virus DNA detection by polymerase chain reaction in plasma from healthy US blood donors and serum from multiply transfused patients from Cameroon. Issue 6 (2nd February 2015) - Phan, Tung Gia; Desnues, Christelle; Switzer, William M.; Djoko, Cyrille F.; Schneider, Bradley S.; Deng, Xutao; Delwart, Eric
<x xml:space="preserve">Abstract</x> BACKGROUND A new Marseilleviridae virus family member, giant blood Marseille‐like (GBM) virus, was recently reported in persons from France in the serum of an infant with adenitis, in the blood of 4% of healthy blood donors, and in 9% of multiply transfused thalassemia patients. These results suggested the presence of a nucleocytoplasmic large DNA virus potentially transmissible by blood product transfusion. STUDY DESIGN AND METHODS To investigate this possibility we tested the plasma from 113 US blood donors and 74 multiply transfused Cameroon patients for GBM viral DNA using highly sensitive polymerase chain reaction (PCR) assays. RESULTS GBM DNA was not detected by nested PCR in any of these 187 human specimens. CONCLUSIONS Further testing is required to confirm the occurrence of human GBM virus infections.